Cor triatriatum dexter: a rare incidentaloma - De Michele, Francesca; Paparella, Maria Teresa; Forte, Valentina; Chieppa, Domenico Riccardo Rosario; Nemore, Francesco; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Cor triatriatum dexter (CTD) is an extremely rare finding resulting from the persistence of the right valve of sinus venosus. It is a congenital cardiac anomaly defined by an abnormal septation of the atrium leading to inflow obstruction to the respective ventricle. Multimodal diagnostic modalities are necessary to characterize it for an optimal patient management. We report the case of a 68-year-old woman who presented to our clinic for further feedback of ventricular ectopic beats.